On the trail of medieval wolves: ancient DNA, CT-based analyses and palaeopathology of a 1000-year-old wolf cranium from the Po Valley (northern Italy) - Iurino D. A.; Cilli E.; Caniglia R.; Fabbri E.; Mecozzi B.; Ciucani M. M.; Sardella R.; Persico D. (Historical Biology, 2022)
The Middle Ages represented a crucial period for the evolutionary history of wolves (Canis lupus), marked by both significant ecosystem changes, especially through the degradation of wooded landscapes and heavy persecution, that drove this species to a dramatic demographic decline. In Europe, informative and well-documented wolf remains from the Medieval Ages are exceptionally rare and are mostly represented by teeth and postcranial elements. In this study, we describe a well-preserved wolf cranium dated to ca. 967–1157 AD from the Po Valley (northern Italy). The specimen was analysed through a multidisciplinary approach including CT-based, ancient DNA, and palaeopathological analyses. Morphological and genetic data supported the assignment of this sample to Canis lupus species. CT-based analyses indicated a typical wolf-like morphology falling into the extant variability of the medium-sized subspecies C. lupus italicus, whereas palaeopathological analyses indicated a severe periodontitis. Phylogenetic analyses showed that the Po valley wolf had a unique and never described mtDNA control region haplotype, testifying variability in the ancient Italian wolf, which has now been lost. This study provides the first comprehensive description of a wolf from the Middle Ages, adding useful information for a deeper knowledge about population dynamics, variability, and diseases of this species.